Vaccine hesitancy among parents in the general population in Sicily (South Italy): A survey study. (13th November 2019) - Ferrante, M; Cristaldi, A; Cormaci, L; Falla, M G; Zuccarello, P; Oliveri Conti, G; Fiore, M
Abstract: Background: Vaccine hesitancy (VH) has become the focus of growing attention because of decreased vaccination rates and increased emergency department use, morbidity, and mortality. VH has not been deeply studied in Sicily. The aim of this study was to estimate the prevalence of VH among parents and to investigate the potential determinants. Methods: We performed a survey from 1 March to 1 June 2018, using a random sample of parents who reported on median 10 year-old children. The parents were recruited in pediatrician's offices and elementary schools. Information pertaining to socio-demographic characteristics, sources of information regarding vaccination and VH was collected. VH was calculated using the Parents Attitudes about Childhood Vaccines (PACV) questionnaire. Associations between VH and predictors were tested using Multivariable Logistic Regression. Results: In total 471 questionnaires were collected, 77.7% of respondents were mothers. Based on the PACV 100-point scale, 73.2% (95% CI: 69.0-77.2) of parents had a 0 to <49 score (low level of VH); and 26.8% (95% CI: 22.8-31.0) had a score of 50 and higher (high level of VH). Internet (66.9%, 95% CI: 62.4-71.1) was the main source of information on vaccination followed by television (29.1%, 95% CI: 25.0-33.4). In the bivariate analyses, VH was associated with education, marital status and occupation, but not with gender and age of parents. In multivariate analyses, highly educated (ORadj = 0.297, 95% CI = 0.141-0.626) and married (ORadj = 0.457, 95% CI = 0.213-0.977) parents were more prone to be nonhesitant, but not so unemployed parents (ORadj = 1.787, 95% CI = 1.083-2.956). Conclusions: The prevalence of VH among the Sicilian parents was comparable with other populations. These results could be an important starting point to support the implementation of effective vaccination strategies. Key messages: Implement interventions and strategies to further understand the issue of VH, to restore trust in authorities and vaccines. Suggest strategies that could improve childhood vaccination rates.